A conceptual framework for community detection, characterisation and membership in a social internetworking scenario. (1st January 2014) - De Meo, Pasquale; Nocera, Antonino; Quattrone, Giovanni; Ursino, Domenico
Social internetworking systems are becoming a challenging new reality; they group together multiple, and possibly heterogenous, social networks. The typical problems of social network research become much more complex in a social internetworking context. In this paper, we propose a conceptual framework, and an underlying model, to handle some of these problems, namely community detection, characterisation and membership in a social internetworking scenario. In order to face them, we must preliminarily investigate a further problem, i.e., user similarity detection.